THE EFFECT OF PEDAGOGICAL COMPETENCE AND ORGANIZATIONAL CULTURE ON CREATIVITY AND ITS IMPLICATIONS ON THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS IN LABUAN DISTRICT, PANDEGLANG REGENCY - Srimarwati, Enong; Rustandi, Tata; Permana, Angrian (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of pedagogical competence and organizational culture on creativity and its implications on the performance of elementary school teachers in Labuan District, Pandeglang Regency. Specifically, this study examines the relationship between personality and organizational culture, the relationship between personality and teacher performance through organizational culture as an intervening variable, the relationship between the work environment and organizational culture, the relationship between the teacher's work environment and organizational culture in Cipeucang District Elementary School, and the relationship between organizational culture and teacher performance. The research method used is quantitative with a descriptive approach and associative survey. The study population consisted of 98 civil servant teachers in Cipeucang District Elementary School, Pandeglang Regency, who also served as research samples. The research instrument was a questionnaire with a Likert scale, while data analysis was carried out using regression techniques using the Smart PLS tool. The results of this study indicate that pedagogical competence and organizational culture have a positive effect on teacher creativity, which in turn improves performance. However, when organizational culture is considered as an intervening variable, personality does not significantly influence teacher performance. Furthermore, organizational culture has been shown to act as an intervening variable, but the work environment does not show a significant effect. These findings emphasize the importance of strengthening pedagogical competence and developing a conducive organizational culture to enhance teacher creativity and performance. This study provides practical implications for elementary school management, particularly in building an organizational culture that supports teacher professionalism.